Cardiac-Autonomic Responses to In-Season Training Among Division-1 College Football Players. Issue 6 (June 2020) - Flatt, Andrew A.; Esco, Michael R.; Allen, Jeff R.; Robinson, James B.; Bragg, Amy; Keith, Clay M.; Fedewa, Michael V.; Earley, Ryan L.
Abstract : Abstract: Flatt, AA, Esco, MR, Allen, JR, Robinson, JB, Bragg, A, Keith, CM, Fedewa, MV, and Earley, RL. Cardiac-autonomic responses to in-season training among Division-1 college football players. J Strength Cond Res 34(6): 1649–1656, 2020—Despite having to endure a rigorous in-season training schedule, research evaluating daily physiological recovery status markers among American football players is limited. The purpose of this study was to determine whether recovery of cardiac-autonomic activity to resting values occurs between consecutive-day, in-season training sessions among college football players. Subjects ( n = 29) were divided into groups based on position: receivers and defensive backs (SKILL, n = 10); running backs, linebackers, and tight-ends (MID-SKILL, n = 11) and linemen (LINEMEN, n = 8). Resting heart rate (RHR) and the natural logarithm of the root mean square of successive differences multiplied by 20 (LnRMSSD) were acquired at rest in the seated position before Tuesday and Wednesday training sessions and repeated over 3 weeks during the first month of the competitive season. A position × time interaction was observed for LnRMSSD ( p = 0.04), but not for the RHR ( p = 0.33). No differences in LnRMSSD between days was observed for SKILL (Tuesday = 82.8 ± 9.3, Wednesday = 81.9 ± 8.7, p > 0.05). Small reductions in LnRMSSD were observed for MID-SKILL (Tuesday = 79.2 ± 9.4, Wednesday = 76.2 ± 9.5, p ⩽ 0.05) and LINEMEN (Tuesday = 79.4 ± 10.5, Wednesday = 74.5 ± 11.5, p ⩽ 0.05). The individually averaged changes in LnRMSSD from Tuesday to Wednesday were related to PlayerLoad ( r = 0.46, p = 0.02) and body mass ( r = −0.39, p = 0.04). Cardiac-parasympathetic activity did not return to resting values for LINEMEN or MID-SKILL before the next training session. Larger reductions in LnRMSSD tended to occur in players with greater body mass despite having performed lower workloads, although some individual variability was observed. These findings may have implications for how coaches and support staff address training and recovery interventions for players demonstrating inadequate cardiovascular recovery between sessions.